Ekonomi Biru, Perubahan Iklim, dan Ketahanan Pangan: Analisis Data Panel - Azzam Robbani (Universitas Persada Indonesia YAI, 2026)
This study explores the intersection between the blue economy and global food security, focusing on twelve Asia-Pacific countries from 2015 to 2021. As the blue economy becomes increasingly vital in sustainable development, particularly in regions reliant on marine resources, this research aims to quantitatively assess how key blue economy factors—such as fish production, government policies, marine biodiversity, and climate change—affect food security outcomes. Using a robust dataset sourced from reputable international organizations like the Food and Agriculture Organization (FAO) and the World Bank, the study applies panel data analysis using the Fixed Effects Model (FEM) based on the Hausman test. The findings reveal that climate change exerts a statistically significant and negative impact on food security, underscoring the vulnerability of food systems to environmental variability, particularly in regions where agriculture and fisheries depend heavily on natural rainfall and stable climatic conditions. Conversely, other blue economy factors—fish production, government policies, and marine biodiversity—do not show a significant direct influence on food security within the scope of this study. This suggests that while these areas hold potential, they may require more targeted and effective policy interventions to enhance their contributions to food security. The study emphasizes the need for policy recommendations that include the promotion of sustainable aquaculture and fisheries management, climate change mitigation strategies, and the development of comprehensive regulatory frameworks. Additionally, engaging local communities in the implementation of Marine Protected Areas (MPAs) is crucial for conserving marine biodiversity and supporting food security.